Tinjauan Yuridis Tindak Pidana Cyber Crime Terhadap Pencemaran Nama Baik Di Kota Makassar (Studi PutusanNo. 255/Pid.Sus/2021/PN.Mks) - Andi Rahmah; Asrul Aswar; Dhea Rezkyah M (Pledoi Law Jurnal, 2023)
ABSTRACT: This type of research is normative law. The data collection technique used is literature study (library research). The data analysis method used in this research is qualitative data analysis. The research results show that (1) The application of substantive criminal law is found in Article 45 paragraph (3) in conjunction with Article 27 paragraph (3) of the Indonesian Law Number 19 of 2016 concerning amendments to the Indonesian Law Number 11 of 2008 concerning Electronic Information and Transactions as a specific regulation. In this case, the defendant is charged with defamation. However, the author disagrees with the Prosecutor's demand because the defendant should be charged with incitement, namely Article 160 of the Criminal Code. (2) The judge's consideration in imposing sanctions on cyber crime perpetrators for defamation is that the judge acquits the defendant because there are elements contained in it that cannot be fulfilled, namely